Channel Estimation and Prediction Based Adaptive Wireless Communication Systems - Al-Shammari, Abeer O.; Salim, Khalifa A.; Abdalla, Mohammed A. (Al-Khwarizmi Engineering Journal, 2012)
Wireless channels are typically much more noisy than wired links and subjected to fading due to multipath  propagation which result in ISI and hence high error rate. Adaptive modulation is a powerful technique to improve the tradeoff between spectral efficiency and Bit Error Rate (BER). In order to adjust the transmission rate, channel state information (CSI) is required at the transmitter side.In this paper the performance enhancement of using linear prediction along with channel estimation to track the channel variations and adaptive modulation were examined. The simulation results shows that the channel estimation is sufficient for low Doppler frequency shifts (